Suppression of intermixing in strain-relaxed epitaxial layers - Leontiou, Theodoros; Tersoff, Jerry; Kelires, Pantelis C. (My University, 2010)
Misfit strain plays a crucial role in semiconductor heteroepitaxy, driving alloy intermixing or the introduction of dislocations. Here we predict a strong coupling between these two modes of strain relaxation, with unexpected consequences. Specifically, strain relaxation by dislocations can suppress intermixing between the heterolayer and the substrate. Monte Carlo simulations and continuum modeling show that the suppression, though not absolute, can be surprisingly large, even at high temperatures. The effect is strongest for a large misfit (e.g., InAs on GaAs) or for thin substrates (e.g., Ge on silicon on insulator).
Keywords: Computer simulation; Continuum mechanics; Germanium; Indium arsenide; Gallium alloys